World politics, globalization and the crisis - Simić Predrag (Međunarodni Problemi, 2013)
In the early 21st century, globalization and the world economic crisis changed the balance of powers between the old (declining) and new (emerging) industrial states replacing the unilateral with a multilateral system of international relations and changing the way in which world politics was functioning. Globalization has increased the number of transnational problems (protection of human environment, international traffic and communications, flows of capital, energy, migrations, etc.) that require global governance. However, these trends also indicate that in the 21st century, international relations and world politics will function in a significantly different manner than they did within the bipolar and unipolar order, which characterized the second half of the 20th century.